Synergistic enhancement of microwave absorption in CNT-NZF CI/epoxy and carbon black/epoxy nanocomposites through dual phase structuring - Idza Riati, Ibrahim; Rodziah, Nazlan; Siti Nor Ain, Rusly; Fadzidah, Mohd Idris; Khamirul Amin, Matori; Ismayadi, Ismail; Ghazaleh, Bahmanrokh; Muhammad Misbah, Muhammad Zulkimi; Nor Hapishah, Abdullah; Muhammad Syazwan, Mustaffa; Arlina, Ali (Elsevier Ltd., 2025)
An efficient microwave absorber is essential for reducing electromagnetic interference in modern technologies. Here we highlight a magnetic-catalyst-assisted route to carbon nanotubes (CNTs): CNTs were grown by CVD using Ni–Zn ferrite/carbonyl iron (NZF/CI) as magnetic catalysts, embedding magnetic nanophases within the CNT network. This magnetic–dielectric coupling increases magnetic loss (μ″) through natural-resonance and eddy-current pathways. When combined with a graded double-layer structure which CNT/epoxy (matching/front) and carbon black (CB)/epoxy (absorbing/back), synergistically optimizing impedance matching and in-layer attenuation across the X- and Ku-bands. Single-layer CNT/epoxy and double-layer CNT/epoxy–CB/epoxy nanocomposites were fabricated and characterized by Raman spectroscopy, field emission scanning electron microscopy (FESEM), and a PNA network analyzer over the X- and Ku-band frequency ranges. Results revealed that the optimized double-layer structure, comprising a 1 mm CNT as a matching layer and a 1 mm carbon black as an absorbing layer, achieved a −10 dB absorption bandwidth of 2.58 GHz and over 99.99 % absorption at 11.14 GHz. Microstructural analysis shows nanosized CB (∼41 nm) uniformly distributed, providing abundant interfacial sites and micro-capacitive contacts that elevate ε″, while entangled CNTs (outer diameter ∼61 nm; spiral/twisted/net-like) promote multiple internal reflections and efficient dissipation. The close contact between CNTs and NZF/CI further strengthens magnetic loss and stabilizes impedance matching. These results demonstrate a cost-effective, magnetic–dielectric double-layer strategy for high-performance and thin microwave absorbers.